A pilot study assessing retinal pathology in psychosis using optical coherence tomography: Choroidal and macular thickness. (May 2018) - Joe, Peter; Ahmad, Meleha; Riley, Gabriella; Weissman, Judith; Smith, R. Theodore; Malaspina, Dolores
Abstract: Mounting evidence supports a genetic-vascular-inflammatory etiology of schizophrenia. The retina provides an indirect assessment of inflammation and degeneration in the brain. In particular, the use of spectral domain optical coherence tomography (SD-OCT) has emerged as a powerful tool for examining single retinal nerve cell layers and the choroid, the vascular layer supplying the outer retina. In this study, choroidal and macular thicknesses were measured in six patients with psychosis with either schizophrenia or bipolar disorder, and in 18 age- and sex-matched healthy controls. Mean choroidal thickness was reduced in psychosis, though not significantly so. There was a statistically significant decrease in macular thickness in psychosis patients predominantly affecting the inner layers of the macula. Significant macular thinning may signal vascular, inflammatory, or degenerative processes that may also be occurring in the brain. This is one of the first studies to examine choroidal thickness in psychosis. Further studies are needed to determine whether the retinal changes in psychosis are correlated with microvascular dysfunction, neuroinflammation, and neurodegeneration. Highlights: The retina serves as "window to the brain". Single retinal cell layers and the choroid can be imaged in detail using spectral domain optical coherence tomography (SD-OCT). Significant inner macular thinning is present in psychotic individuals compared to healthy controls. Choroidal thickness is a potentially novel retinal biomarker for psychosis. Chorioretinal thinning may represent primary disturbances of the neurovasculature or degeneration in schizophrenia.